PENGARUH WORD OF MOUTH, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSANPEMBELIAN: (Studi pada Warung Nasi Urang Sunda Khas Cianjur di Bumi Serpong Damai) - Wulandari Wulandari; Kartini Istikomah (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The rapid competition in the food and beverage industry is characterized by the number of companies engaged in fast food. This is due to the large number of food and beverage industries which make one the contributing factors in making purchasing decisions. The purpose of this study was to determine and examine the effect of word of mouth, price and product quality on purchasing decisions at Warung Nasi Uranng Sunda Khas Cianjur in Bumi Serpong Damai. The sample used in this study indicates that word of mouth has on influence on purchasing decisions, while price and product quality have a significant effect on purchasing decision.